The Effect of Giving Watermelon Fruit on Increasing HB Levels in Adolescents - Masruroh Masruroh; Heny Noor Wijayanti; Yelli Yani Rusyani; Ayu Fitriani; Sesillia Sesillia (Journal of Midwifery, 2023)
Research Background : WatermelonÂ is known to be one of the best fruits for increasing haemoglobin level. It is rich in vitamin C and iron content, which help in better absorption of iron. As per USDA, 100 grams of watermelon contains 0.2 milligrams of iron. In young women, iron is also needed to replace iron during menstruation.Research Objective: to determine the effect of giving watermelon fruit to increasing HB levels in adolescents.Research Methods: Quantitative research uses the quasy-experiment method with a pre-test-post test design. The number of samples in this study were 14 adolescents according to the inclusion criteria using a purposive sampling technique. Intervention in the form of 200 grams of watermelon flesh for 14 days. Analysis using paired t-test.The results of the study: It is known that the average HB level in adolescents before giving watermelon is 12.41 g/dl, while the hemoglobin level in adolescents after giving watermelon is known to be 13.01 g/dl. The data obtained were analyzed by Free T test with a significance level of <0.05 and obtained p 0.271. The results of the difference in the average hemoglobin level before and after giving the watermelon showed an increase of -1.71 Â± 0.52 gr/dl.Conclusion: So it can be concluded that there is no effect of giving watermelon fruit to increasing HB levels in adolescents.